Answer:
(7, 1/2)
Step-by-step explanation:
Multiply second equation by 2 and subtract.
3x - 4y = 19
- (4x - 4y = 26)
You get -x = -7
x = 7
Substitute x into any equation.
3(7) - 4y = 19
21 - 4y = 19
-4y = -2
y = 1/2
Answer:
69 :D
Step-by-step explanation:
its a funny number :v
Step-by-step explanation:
Total surface area of cuboid= 2(lb+bh+hl)
= 298ft²=2(28+4x+7x)
= 149=28+11x
= 121=11x
= 11=x
Answer:
Step-by-step explanation:
the difference is 56 because if you add and divide them by 3 and -2 you will get 56
Together I think it’s the same way that you can get the one to the one you have on your computer problems you have no proof that I have it on my computer problems I have lost all the same information I I don’t have any proof that you are in my account so so much you have to pay for it and I’m sorry you don’t know where I can get you I know I